2015
DOI: 10.1097/opx.0000000000000600
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Confocal Microscopy in Dry Eye Treated with Corticosteroids

Abstract: Laser scanning confocal microscopy examination of DCD allows detection of treatment-related inflammation changes and shows previously unknown associations between confocal finding and symptoms improvement after treatment. These promising preliminary data suggest the need for future studies testing the predictive value of DCD for a clinical response to topical corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 34 publications
(65 reference statements)
1
58
0
Order By: Relevance
“…149 In contrast another study showed that corneal sub-basal nerve fiber length was similar in the patient group that showed clinical improvement and the patient group with no clinical improvement following treatment. 151 Notably, though nerve length was similar, sub-basal dendritic cell density was decreased in the patient group that responded positively to treatment. 151 Nonetheless, including corneal nerve changes in DED clinical trials, would require extensive instruction for each site and support of automated analysis.…”
Section: Point Of Care Biomarkersmentioning
confidence: 89%
See 2 more Smart Citations
“…149 In contrast another study showed that corneal sub-basal nerve fiber length was similar in the patient group that showed clinical improvement and the patient group with no clinical improvement following treatment. 151 Notably, though nerve length was similar, sub-basal dendritic cell density was decreased in the patient group that responded positively to treatment. 151 Nonetheless, including corneal nerve changes in DED clinical trials, would require extensive instruction for each site and support of automated analysis.…”
Section: Point Of Care Biomarkersmentioning
confidence: 89%
“…148155 This has been studied using in vivo confocal microscopy, which allows visualization of the layers of the cornea. 156 Some effort has been made to identify potential predictive anatomic biomarkers on the corneal surface and the MGs, primarily using confocal microscopy.…”
Section: Point Of Care Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15][16][17] Supporting the role of inflammation in the pathogenesis of DED is a body of clinical evidence that antiinflammatory therapies, including corticosteroids and cyclosporine, reduce inflammatory markers, and provide symptomatic improvement. [18][19][20][21] The aim of the study was to characterize tear composition in humans having hyperosmolar tears, to determine whether tear hyperosmolarity is associated with specific changes to tear cytokines that could be useful as a diagnostic clinical marker for DED.…”
mentioning
confidence: 99%
“…Topical corticosteroids bind and activate the cytosolic glucocorticoid receptor and promote anti-inflammatory gene expression in leukocytes and lymphocyte apoptosis [84-85]. New biomarkers, such dendritic cell density, assessed via confocal microscopy, have been shown to correlate with treatment-related inflammation changes and may help predict response to topical corticosteroids [86]. Although the long-term use of corticosteroids has complications, a brief course has proven effective in DE [84, 87].…”
Section: Therapeutic Interventionsmentioning
confidence: 99%